Five essential habits for a healthy brain / Nur Sabiha Md Hussin - Md Hussin, Nur Sabiha (Faculty of Pharmacy, 2024)
The human brain is the command center for the nervous system, enabling thoughts, memory, movement, and emotions through a complex function that represents the pinnacle of human biological evolution (Maldonado KA & Alsayouri K, 2023). Brain health is defined as the ability to perform cognitive processes (Centers for Disease Control and Prevention, 2009). According to the American Heart Association, optimal brain health refers to the level of performance considered average for individuals of a certain age without any known brain or organ system disorders. It can be assessed by the degree of cognitive function decline or the ability to carry out desired activities (Gorelick et al., 2017).